2020
DOI: 10.1183/13993003.01654-2019
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension with below threshold pulmonary vascular resistance

Abstract: Pulmonary vascular resistance (PVR) >3 Wood units is a criterion of the haemodynamic definition of pulmonary arterial hypertension (PAH). However, this cut-off is conservative and arbitrarily defined. Data is lacking on the natural history, response to therapy and survival of patients diagnosed with precapillary pulmonary hypertension (PH) with mild or borderline elevation of PVR.In Australia, PAH therapy could be prescribed solely on mean pulmonary arterial pressure (PAP) and pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…When patients with normal or only mildly elevated PVR were excluded, we did not observe a difference in relationship between PVR and CI in patients with SSc-PAH suggesting that increased stiffness of the pulmonary arterial bed is unlikely to be responsible for differences in outcomes. The patients with PVR between 2 and 3 also appear to be at risk of progression to PH [ 21 ], which seems to be also observed in our cohort.…”
Section: Discussionsupporting
confidence: 73%
“…When patients with normal or only mildly elevated PVR were excluded, we did not observe a difference in relationship between PVR and CI in patients with SSc-PAH suggesting that increased stiffness of the pulmonary arterial bed is unlikely to be responsible for differences in outcomes. The patients with PVR between 2 and 3 also appear to be at risk of progression to PH [ 21 ], which seems to be also observed in our cohort.…”
Section: Discussionsupporting
confidence: 73%
“…Results extrapolated from this study could also be used to guide national screening programmes for detecting early stage PAH, already underway in some countries, including France [13]. RATWATTE et al [9] are to be congratulated on these important data, which help build a much-needed framework for contemporising the PAH haemodynamic criteria relative to PVR. These findings should stimulate additional investigations using definitive clinical research methodologies, which were not yet available at the time the current work was assembled, to understand the association between PVR <3.0 WU and therapeutic response in PAH.…”
mentioning
confidence: 89%
“…In this issue of the European Respiratory Journal, RATWATTE et al [9] add a key piece to the PVR puzzle by leveraging the unique clinical practice patterns in Australian and New Zealand, in which PVR ⩾3.0 WU is not obligatory for treating PAH. The investigators assembled data for 2378 PAH patients enrolled in the PHSANZ registry between 2011 and 2018, and focused on 82 patients for whom the PVR was <3.0 WU.…”
mentioning
confidence: 99%
“…JAAFAR et al ) who were all treated with PAH-specific therapy. They found that this haemodynamic picture was associated with impaired function and reduced survival but was also associated with functional response to PAH-specific therapy [79].…”
Section: Impact Of the Sixth Wsph Definitionmentioning
confidence: 99%
“…In those patients with a mPAP ⩾19 mmHg and PAWP ⩽15 mmHg, the PVR threshold above which the hazard ratio for mortality increased was 2.2 WU. RATWATTE et al[79] recently presented data on 82 patients (42 with CTD) with mPAP ⩾25 mmHg, PAWP ⩽15 mmHg but PVR <3 WU (median (interquartile range) 2.2 (1.9-2.7) WU…”
mentioning
confidence: 99%